OVERVIEW OF PT UTSMANIAH HANNIEN TOUR'S LEGAL LIABILITY FOR CONGREGANTS WHO ARE NOT DEPARTED - Cucuk Endarto (Sean Institute, 2021)
The purpose of this study is to determine the issues that arise in the legal relationship that exists between PT. Utsmaniah Hanien Tour, a travel service firm, and its customers, as well as the manner in which PT. Ottoman Hanien Tour is responsible to its customers. This study is a normative piece of juridical and legal research that makes use of two different types of techniques, namely the legislative approach and the legal concept analysis approach. The author of this piece comes to the conclusion that according to Regulation Number 8 of 2018 Issued by the Minister of Religion of the Republic of Indonesia Concerning the Organization of Umrah Worship Trips, in the event that sanctions are suspended or revoked, the Umrah Worship Travel Organizer (PPIU) is obligated to return the Cost of Organizing the Umrah Worship (BPIU) to the congregation. This obligation is stated in the event that sanctions are suspended or revoke PT. The Ottoman Hannien Tour must be held liable for the loss of the Umrah pilgrims who were not dispatched on the tour..